Baby Steps: The Gender Division of Childcare during the COVID-19 Pandemic - Almudena Sevilla; Sarah Smith (Institute of Labor Economics (IZA), 2020)
The COVID19 pandemic has caused shocks to the demand for home childcare (with the closure of schools and nurseries) and the supply of home childcare (with many people not working). We collect real-time data on daily lives to document that UK families with young children have been doing the equivalent of a working week in childcare. Women have been doing the greater share, but overall, the gender childcare gap (the difference between the share of childcare done by women and the share done by men) for the additional, post-COVID19 hours is smaller than that for the allocation of pre-COVID19 childcare. However, the amount of additional childcare provided by men is very sensitive to their employment – the allocation has become more equal in households where men are working from home and where they have been furloughed/ lost their job. There are likely to be long-term implications from these changes – potentially negative for the careers of parents of young children; but also, more positively for some families, for sharing the burden of childcare more equally in the future.
Keywords: J21; J22; J24; J33; J63; 330; gender; childcare; COVID-19; Coronavirus